Social-philosophical and educational aspects of globalization - KRYMETS, L.V. (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article provides total globalization, the problem of managing worldprocesses, including world culture and world public opinion, becomes one of thecentral objectives of humankind in the development of modern education